Patient satisfaction and quality of life after septoplasty in adults: literature review - Wójcik, Bartłomiej; Wójcik, Jakub; Błaszczak, Ewa; Gil, Krzysztof; Małachowski, Aleksander; Wójcik, Tomasz; Dryżałowski, Piotr; Steć, Sara; Czajka, Katarzyna (Journal of Education, Health and Sport, 2025)
Background: Septoplasty is a common surgical procedure designed to correct a deviated nasal septum and relieve symptoms of nasal obstruction. While the primary goal of the surgery is to improve nasal airflow, patient satisfaction and quality of life (QoL) have become important measures of surgical success. Understanding the impact of septoplasty on QoL is essential to optimise patients’ outcomes and refine treatment approaches. Despite its widespread use, number of high-quality studies have been limited. However, in recent years there have been a growing interest in assessing its effectiveness using objective and patient-reported outcomes. Objective: The aim of this literature review is to analyse the effectiveness of septoplasty, including the impact of septoplasty on patient satisfaction and quality of life, and to assess predictors of surgical success. State of knowledge: Septoplasty is a surgical procedure aimed at correcting a deviated nasal septum to improve nasal airflow and relieve obstruction. Recent studies show, that septoplasty leads to significant improvement in nasal breathing, sleep quality, daily functioning, mental state and olfactory function. Psychological factors, preoperative expectations and degree of nasal deviation have been identified as key determinants of surgical outcome. Conclusion: Septoplasty is an effective procedure that leads to significant improvements in quality of life and general satisfaction from surgery. Several factors have been identified that influence surgical outcome including patient mental state, patient expectation, severity of septal deviation and surgical technique. To optimise results, surgeons should focus on refining surgical techniques, patient selection and management of patients’ expectations.